COMPREHENSIVE MIDWIFERY CARE TO MRS “S” G1P0A0 FEET SLUMP WITH HYDROTHERAPY AND PAIN AT ONE PERIOD OF LABOR WITH MASSAGE EFFLEURAGE AT “BI” CLINIC CIPATAT WEST BANDUNG DISTRICT - Hasanah, Uswatun; Fatonah HS, Sofa; Sarikah , Iik; Karwati , Karwati (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. Leg swelling is an inconvenience that often occurs in the third trimester of pregnancy and can be treated with hydrotherapy to reduce discomfort to the mother. Pain associated with childbirth is one of the most intense forms of pain that a woman in labor experiences. So it requires care to reduce pain and discomfort in the labor process, the method for pain reduction is by massage effleurage. Findings at BI” Clinic from 50 pregnant women as many as 37 pregnant women (75%) experienced leg swelling discomfort. This study aims to determine the effect of the intensity of leg swelling after hydrotherapy on leg swelling in the third trimester, effleurage massage in the first stage of labor. Methods. The study method sed is a case study by conducting an assessment to provide care. The study subject Mrs. "S" who experienced leg swelling in the third trimester of pregnancy and was given hydrotherapy intervention for 4 days was given routinely 2 times a day with a duration of 15 minutes, in the first stage of labor she was given 2 times effleurage massage care for 15 minutes in 30 minutes. Results & Analysis. The results of the case study, namely Hydrotherapy, obtained an effect on reducing the level of swelling in the legs, in the first stage of labor, effleurage massage was given, after being given care there was an effect of decreasing pain levels, the mother felt comfortable and the intensity of pain was reduced. Discussion. The conclusion of the case study is that after hydrotherapy care, the swelling of the mother's legs decreases, then after being given effleurage massage in the first stage of labor the intensity of pain is reduced. It is recommended to remove “BI” clinic to further improve care, especially for pregnant women with swelling discomfort in the legs and care for mothers in labor with labor pains in the first stage.